Radicalization within: Sri Lankan Muslims in the Age of ISIS - Wickramasinghe, Ashan Y. (University of Colombo, 2015)
While radicals exist on the fringes of every religion, fears about the rise of radical Islamism have become especially rampant over the years. It could be contended that radicalization does not spread unless a space is provided for it to breed. Today, radical Islamism has taken a life of its own and has become the default ideology for minor elements of Muslims around the world. There is no single explanation for radicalization largely because different individuals arrive at radicalism through unique routes. Islamist radicalism is a complex phenomenon. Its meaning and application varies from individual to individual and from organization to organization and is unconstrained by borders or a single ideology. However, understanding the drivers of radicalization is imperative because they have become prime tactics for radical groups to recruit individuals. No region in the world is immune to this occurrence. Sri Lanka is not a country that is widely known as a supporter of trans-border religio-centric turmoil, nor are her citizens traditionally been overt supporters of such conflicts.
Keywords: Radicalization within: Sri Lankan Muslims in the Age of ISIS